PEMBUATAN BATA RINGAN BERBAHAN DASAR LIMBAH PENGOLAHAN EMAS TRADISIONAL DI PROPINSI NTB - Dwi Sabda Budi Prasetya; Seto Priyambodo; Sukainil Ahzan (Lensa: Jurnal Kependidikan Fisika, 2016)
Research on the manufacture of lightweight brick with basic material waste processing of goldin the province of West Nusa Tenggara has been done. This research is very important because most of the people in NTB separate gold by amalgamation and cyanidation methods. Processes that do this will result in hazardous waste on the environment so that the need for countermeasures. The purpose of this research is to create a lightweight bricks made of waste processing of gold which has a strong press that meets national standards. This research was conducted through two stages, namely 1) Stage of light brick making, 2) Phase compressive strength test light brick production. The results showed that lightweight bricks made with waste raw gold processing and cement with a ratio of 3: 1 has a compressive strength of 7.80 kg / cm2. These results demonstrate compliance with national standards, namely 7.83 kg / cm2 so that the product of this research can be said to be feasible.